Childhood trauma is associated with a specific admixture of affective, anxiety, and psychosis symptoms cutting across traditional diagnostic boundaries. Issue 6 (2nd October 2014) - van Nierop, M.; Viechtbauer, W.; Gunther, N.; van Zelst, C.; de Graaf, R.; ten Have, M.; van Dorsselaer, S.; Bak, M.; ,; van Winkel, R.
Abstract : Background: Meta-analyses link childhood trauma to depression, mania, anxiety disorders, and psychosis. It is unclear, however, whether these outcomes truly represent distinct disorders following childhood trauma, or that childhood trauma is associated with admixtures of affective, psychotic, anxiety and manic psychopathology throughout life. Method: We used data from a representative general population sample (NEMESIS-2, n = 6646), of whom respectively 1577 and 1120 had a lifetime diagnosis of mood or anxiety disorder, as well as from a sample of patients with a diagnosis of schizophrenia (GROUP, n = 825). Multinomial logistic regression was used to assess whether childhood trauma was more strongly associated with isolated affective/psychotic/anxiety/manic symptoms than with their admixture. Results: In NEMESIS-2, largely comparable associations were found between childhood trauma and depression, mania, anxiety and psychosis. However, childhood trauma was considerably more strongly associated with their lifetime admixture. These results were confirmed in the patient samples, in which it was consistently found that patients with a history of childhood trauma were more likely to have a combination of multiple symptom domains compared to their non-traumatized counterparts. This pattern was also found in exposed individuals who did not meet criteria for a psychotic, affective or anxiety disorder and who did not seek help for subclinical psychopathology. Conclusions: Childhood trauma increases the likelihood of a specific admixture of affective, anxiety and psychotic symptoms cutting across traditional diagnostic boundaries, and this admixture may already be present in the earliest stages of psychopathology. These findings may have significant aetiological, pathophysiological, diagnostic and clinical repercussions.